Structure-Activity Relationships for the Interactions of 2’- and 3’-(O)-(N-Methyl)anthraniloyl-Substituted Purine and Pyrimidine Nucleotides with Mammalian Adenylyl Cyclases - Pinto, Cibele (2011)
Membranous adenylyl cyclases (ACs) play a key role in signal transduction and are promising drug targets. In previous studies we showed that 2’,3’-(O)-(N-methylanthraniloyl) (MANT)-substituted nucleotides are potent AC inhibitors. The aim of this study was to provide systematic structure-activity relationships for 21 (M)ANT-substituted nucleotides at the purified catalytic AC subunit heterodimer VC1:IIC2, the VC1:VC1 homodimer and recombinant ACs 1, 2 and 5. (M)ANT-nucleotides inhibited fully activated VC1:IIC2 in the order of affinity for bases hypoxanthine > uracil > cytosine > adenine ~ guanine ≫ xanthine. Omission of a hydroxyl group at the 2’ or 3’-position reduced inhibitor potency as did introduction of a γ-thiophosphate group or omission of the γ-phosphate group. Substitution of the MANT-group by an ANT-group had little effect on affinity. Although all nucleotides bound to VC1:IIC2 similarly according to the tripartite pharmacophore model with a site for the base, the ribose, and the phosphate chain, nucleotides exhibited subtle differences in their binding modes as revealed by fluorescence spectroscopy and molecular modelling. MANT-nucleotides also differentially interacted with the VC1:VC1 homodimer as assessed by fluorescence spectroscopy and modelling. Similar structure-activity relationships as for VC1:IIC2 were obtained for recombinant ACs 1, 2 and 5, with AC2 being the least sensitive AC isoform in terms of inhibition. Overall, ACs possess a broad base-specificity with no preference for the “cognate” base adenine as verified by enzyme inhibition, fluorescence spectroscopy and molecular modelling. These properties of ACs are indicative for ligand-specific conformational landscapes that extend to the VC1:VC1 homodimer and should facilitate development of non-nucleotide inhibitors.